The crisis of neoliberal globalization and labor markets in Andalusia (Spain) - Caravaca, Inmaculada; González-Romero, Gema (Pontifícia Universidade Católica de São Paulo, 2017)
The profound changes in economic, labor, social and institutional structures that have been occurring since the late 20th century have become faster, deeper and more complex over the last decade, as a crisis of exceptional depth has been generated. Although it began as a financial crisis, it has evolved to become systemic. This crisis, in addition to exposing the frailties of the system, is causing new socioeconomic and territorial inequalities. The aim of this paper is to analyze the effects of the crisis on labor markets of the cities of Andalusia that have more than 20,000 inhabitants, trying to detect whether there have been changes in the territorial model of this region, which is considered peripheral both in the Spanish and European spheres.